Gender-influenced Parents' Investment in Children's Education - Hana Pacáková; Michal Ježek (Czech Pedagogical Society, 2016)
The paper focuses on gender-influenced differences in parents' social, time, economic and emotional investment in their children's education. The study is based on various articles and publications, predominantly from the USA, that could guide the direction for further investigation in the field. In the Czech Republic, this type of study is still scarce. Current papers focus mostly on influence of the education system itself, differences in learning abilities or ideas about the future professional path. Needless to say, the subject of influence of the parental investment on children's educational performance is not investigated. The study shows, especially on the example of the USA, that parents participate more in the education of their daughters, in terms of parental involvement (in some aspects) and financial transfers. These findings are then compared to the situation in economically similar countries of the South-East Asia, where the traditional patriarchal system of upbringing children is still very strong and influences the educational aspirations of boy and girl students. The discussed studies and their findings support the claim of gender differentiation in educational support, when it comes not only to financial transfers or emotional investment, but also the choice of school subjects.